Pemberdayaan dan Peningkatan Keterampilan bagi Orang Tua dan Elemen Sekolah Berbasis Video dalam Pencegahan Bullying dan Tantrum pada Anak Berkebutuhan Khusus - Rizky Pratiwi; Kens Napolion; Mikawati; Nur Hikma; Nur Fadilah (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
Children with special needs are very vulnerable to becoming victims of bullying. Bullying is a form of child or adolescent violence that is now increasingly common. This activity aims to empower parents and school elements and improve skills (teachers and education staff) in handling and preventing bullying and temper tantrums in children with special needs so as to create a conducive and controlled atmosphere for learning activities and help children with special needs achieve a good level of health. optimal. The activity was carried out at the Partner SLB-C YPPLB Makassar location using the method of providing video-based health education about preventing bullying in children with special needs and short training in handling tantrums in autistic children. The number of participants was 30 people. It was carried out using the method of providing video-based health education about preventing bullying in children with special needs and short training in handling tantrums in autistic children. The results of the activities after the activities were carried out, in the school element, both teachers and parents of students experienced increased knowledge regarding bullying and tantrums and were able to handle children with special needs who experienced tantrums better. In addition, a task force unit was formed to deal with bullying in target schools as partner of the public service.